Re-Design Klinik Bersalin “Bidan Jeanne” di Kota Depok Jawa Barat - Nindya Ayu Widyanugrah; Yusita Kusumarini; Anik Rakhmawati (Intra, 2018)
Maternity Clinic is a place that provides professional services related to pregnancy, ranging from control of uterus, childbirth, consultation, pregnancy exercise, to postpartum control. The design of maternity clinics with homey concept so that patients do not feel tense and feel comfortable. The maternity clinic